Analisis Kemudahan Penggunaan pada Antarmuka Pengguna Game Horor GhostyGhost menggunakan System Usability Scale - Sattu, Junita; Filza, Muhammad Fairul; Haryoko (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This research aims to evaluate the usability of the user interface in the horror game “GhostyGhost” using the System Usability Scale (SUS) method. The game is designed to create an immersive gaming experience through visual and aesthetic elements that support a horror atmosphere. In this research, 20 respondents were purposively selected to play the game, complete specific tasks, and fill out an SUS questionnaire consisting of 10 statements. This method allows for the assessment of usability aspects such as ease of use, efficiency, and satisfaction. Results showed that “GhostyGhost” achieved an average SUS score of 71.62, categorized as